Polymeric bio-based nanodispersed admixtures for the production of hydrophobic Portland cement mortars - Ševčík, Radek; Kolář, Martin; Pokorný, Jaroslav; Zárybnická, Lucie; Honzíček, Jan; Machotová, Jana (Frontiers in Built Environment, 2025)
A current trend in the construction industry involves the development and employment of eco-friendly, durable, and sustainable materials. Numerous admixtures, including various polymers, are used to modify the properties of cement. Nonetheless, their effectiveness and environmental impacts are still a matter of discussion. In this context, this work was focused on the application of innovative vegetable oil-based polymeric nanodispersed admixtures, synthesized following green chemistry principles, such as using water as a solvent. The synthesized bio-based latex admixtures were incorporated with 30 wt% of vegetable oil-based monomers derived from camelina, linseed, and rapeseed oils. The produced ordinary Portland cement fine-grained mortars, containing 0.1 wt% of each bio-based latex admixture, were thoroughly examined using several instrumental methods, such as isothermal calorimetry and scanning electron microscopy, to gain a comprehensive understanding of the roles of bio-based latex admixtures on the physical, mechanical, and microstructural properties of the examined specimens. It was found that the addition of bio-based latex admixtures led to changes in the hydration process, mineralogical composition, and liquid water transport. For example, the water absorption coefficient was found to be approximately 40% lower compared to cement mortars produced using a reference latex additive without the vegetable oil-based component. Moreover, cement mortars with a bio-based latex admixture containing camelina oil exhibited comparable compressive strength to those produced solely from ordinary Portland cement. Thus, the newly developed bio-based polymeric nanodispersion represents a new class of environmentally friendly admixtures that may be effectively utilized for water-loaded structures.